Steven Universe. [videorecording (DVD)] [Vol. 1], Gem glow - Sugar, Rebecca, 1987- ([Publisher not identified], 2015)
Believe in Steven! Steven Universe is a half-human, half-Gem hero who's learning to save the world with the magical powers that come from his belly button. Steven may not be as powerful as the Crystal Gems. Or as smart. But that doesn't stop him from joining Garnet, Amethyst and Pearl on their magical adventures -- where Steven always finds a surprising way to save the day.